Implementation of Budget Efficiency Policy on the Performance of State Civil Apparatus in the Secretariat of the Banjar City DPRD - Ripal Fahri Riyadin; Astri Anjani; Diani Ayurika Putri; Ghaitsa Shayfa Ramdini; Ii Sujai (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study explores the implementation of budget efficiency policies and their impact on performance within the Secretariat of the Regional People's Representative Council (DPRD). The background of this research arises from the need for transparent and efficient public financial management, particularly in public organizations. The DPRD Secretariat functions as a support system for the legislative, budgeting, and supervisory roles of the DPRD, thus bearing significant responsibility in ensuring effective budget utilization. The objective of this study is to examine how the budget efficiency policy is implemented, the factors that support and hinder its execution, and the extent to which this policy contributes to improving the performance of the DPRD Secretariat. The research employs a qualitative descriptive methodology with a case study approach. Data collection was conducted through in-depth interviews with relevant officials and staff at the DPRD Secretariat, participatory observation, and analysis of documents and financial reports. The findings indicate that the implementation of the budget efficiency policy in the DPRD Secretariat has been carried out through various approaches, including cost savings in operational expenses, rationalization of activities, and optimization of resource utilization. However, several challenges were identified, such as limited comprehensive socialization, dissatisfaction with changes, and a lack of skilled human resources in performance-based budget management. Overall, the budget efficiency policy demonstrates a positive relationship with performance improvement in certain aspects, particularly in financial accountability and transparency. Nevertheless, its impact on productivity and service quality still requires enhancement. This study recommends strengthening leadership commitment, enhancing human resource capabilities, and improving systems and procedures in the implementation of budget efficiency policies to achieve better performance in the DPRD Secretariat.